TINGKAT KESTABILAN LERENG PADA PERISTIWA GERAKAN TANAH DI SEPANJANG JALAN WILAYAH KONSERVASI KARANGSAMBUNG - Raharjo, Puguh D (2019)
Karangsambung is a sub district located in Kebumen Regency, it is a hill area with many usedfor Perhutani plantation and pine land. Many landform changes begin to be carried out alongwith the increasing human population.It is started from the plantation area conversion intothe settlement, and many slopes-cutting to widen the road as access links between thevillages. The land use changes are the landslides cause in this region. By geotechnical testexpected to find out the erosion cause and find out the prevention process. From thelaboratory test results is known that in the several disaster points soil types are high plasticityclay (CH), high plasticity silt (MH) and passive silt (ML) with the water content ranging from30% - 70%. From the clay activity level is classified as inactive - normal level and low – mediumdevelopment level. Based on the value safety factor (Fs) results calculation < 1 is mean thatincludes the labile or landslide slope. By the flow pattern regulation system and change steepslopes into the terraces, it is expect able to reduce the land movement disaster in this region.